2015
DOI: 10.13189/azb.2015.030102
|View full text |Cite
|
Sign up to set email alerts
|

Role of Different Thymus Essential Oils on Feeding Performance of Leptinotarsa decemlineata Say, 1824 (Chrysomelidae: Coleoptera)

Abstract: The Colorado potato beetle, Leptinotarsa decemlineata Say, 1824 (Chrysomelidae: Coleoptera), is a major problem for conventional potato production in all over the world. Bioactive molecules that originated from plants, have long been claimed as alternatives to synthetic chemicals for pest management Similarly, we investigated antifeedant effect of essential oils obtained from three different Lamiaceae species; Thymus transcaucasicus RONNIGER, Thymus pseudopulegioides KLOKOV and DES.-SHOST, Thymus leucotrichus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…Antifeedant activity of EOs was achieved at lower doses when compared to water and methanolic extracts, which can be explained by differences in composition and the concentrations of active ingredients. Comparing our results on the AFI obtained after 3 days of L. decemlineata exposure to 0.5% concentration of Tanacetum EOs with the results of other authors revealed that Tanacetum EOs were stronger antifeedants than T. leucotrichus EO and the methanolic extract of Humulus lupulus (Gökçe et al ., 2012; Bekircan et al ., 2015), while the hexane-ethylacetate-methanolic extracts of Achillea millefolium and H. lupulus induced similar antifeedant response (Alkan et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Antifeedant activity of EOs was achieved at lower doses when compared to water and methanolic extracts, which can be explained by differences in composition and the concentrations of active ingredients. Comparing our results on the AFI obtained after 3 days of L. decemlineata exposure to 0.5% concentration of Tanacetum EOs with the results of other authors revealed that Tanacetum EOs were stronger antifeedants than T. leucotrichus EO and the methanolic extract of Humulus lupulus (Gökçe et al ., 2012; Bekircan et al ., 2015), while the hexane-ethylacetate-methanolic extracts of Achillea millefolium and H. lupulus induced similar antifeedant response (Alkan et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown antifeeding and avoidance behaviours of L. decemlineata in response to different plant extracts and EOs (González-Coloma et al ., 2006; Pavela, 2010; Gökçe et al ., 2012; Bekircan et al ., 2015). These types of behaviours are induced by compounds that hinder recognition of host-indicating odours and thus host acceptance for oviposition and feeding (Schröder and Hilker, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Essential oils obtained from several plant species belongs to Labiatae family in Turkey has a potantial to pest control and antifeedant affect. Studies have been conducted to determine effect of these essential oils on both eggs, adults and larvae of pests [7,8,9]. In the literature, plant extracts and essential oils obtained from M. longifolia subsp.…”
Section: Introductionmentioning
confidence: 99%